DETERMINAN KEBERHASILAN ASI EKSKLUSIF PADA IBU BEKERJA DI WILAYAH KERJA PUSKESMAS PAYUNG SEKAKI - suryani, linda (JURNAL HEALTH REPRODUCTIVE, 2016)
Â Nutrition insecurity occurs in infants because not only foods less also because of a mother (breastfeeding) many replaced by formula milk that way and number which is not meet the needs. Factors affect the exclusive breastfeeding is knowledge mother, education, the social and cultural , promotion of infant formula, attitude or behavior mother, age, employment, maternal health, and support health workers. The purpose of this research is to know determine influence the success of exclusive breastfeeding in mothers working in the work area payung sekaki of public health care. This study design is analytic cross sectional. Independent variebel such as age, parity, education, family income, knowledge, motivation, support health workers, support partners and dependent variable is exclusive breastfeeding working mothers. The population 265 people and samples 90 respondents using purposive sampling technique. The instrument used is questionaire. Results of the study were calculated using statistical test Chi-Square showed all the factors influencing the success of exclusive breastfeeding working mothers among others,Â  knowledge (P value 0.041), internal motivation (P Value 0.000), the support of health workers (P value 0.036), and support partners ( P value 0.008). From the multivariate analysis of several factors which are the most dominant factor affecting the success of exclusive breastfeeding in mothers work is internal motivation to value (RP) 26 and P.Value 0.000. The higher the motivation of working mothers in exclusive breastfeeding will affect 26 more than those who have low motivation. The need of holding support and health promotion to the public about the importance of exclusive breastfeeding for infants.